2021
DOI: 10.1038/s41392-021-00822-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 induces new-onset insulin resistance and lipid metabolic dysregulation via regulation of secreted metabolic factors

Abstract: Abnormal glucose and lipid metabolism in COVID-19 patients were recently reported with unclear mechanism. In this study, we retrospectively investigated a cohort of COVID-19 patients without pre-existing metabolic-related diseases, and found new-onset insulin resistance, hyperglycemia, and decreased HDL-C in these patients. Mechanistically, SARS-CoV-2 infection increased the expression of RE1-silencing transcription factor (REST), which modulated the expression of secreted metabolic factors including myelopero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 48 publications
4
64
2
2
Order By: Relevance
“…One of the most known and prevalent factors influencing COVID-19 disease progression [ 17 ] is hyperglycemia. COVID-19 disease may cause prolonged uncontrolled elevated blood glucose level [ 18 ] due to COVID-19-induced insulin resistance [ 19 ] and COVID-19-impaired insulin production [ 20 ]. Contrary to COVID-19 non-survivors, patients with positive COVID-19 outcome showed the ability to normalize energy metabolism during the first week of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most known and prevalent factors influencing COVID-19 disease progression [ 17 ] is hyperglycemia. COVID-19 disease may cause prolonged uncontrolled elevated blood glucose level [ 18 ] due to COVID-19-induced insulin resistance [ 19 ] and COVID-19-impaired insulin production [ 20 ]. Contrary to COVID-19 non-survivors, patients with positive COVID-19 outcome showed the ability to normalize energy metabolism during the first week of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our observations, a case report described the occurrence of DM following SARS-CoV-2 infection [ 49 ]. Emerging evidence supports that SARS-CoV-2 may induce hyperglycemia [ 50 ] and new-onset insulin resistance [ 51 ]. More studies are needed to better understand the roles and mechanisms of SARS-CoV-2 infection and COVID-19 in the initiation and progression of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…New-onset hyperglycemia, worsening of pre-existing hyperglycemia, or even ketoacidosis has been seen in COVID-19 patients in an acute, inpatient setting [4]. The issue of hyperglycemia also has been seen to persist in some patient populations following both serious and mild cases of COVID-19 infection, indicating a possible long-term impact of the virus [5]. One prospective study observed patients while in the hospital and then followed up three and six months after discharge.…”
Section: Discussionmentioning
confidence: 99%